2016
DOI: 10.1016/j.ajpath.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Drives Retraction, Stiffening, and Nodule Formation via Cytoskeletal Machinery in a Three-Dimensional Culture Model of Aortic Stenosis

Abstract: In calcific aortic valve disease, the valve cusps undergo retraction, stiffening, and nodular calcification. The inflammatory cytokine, tumor necrosis factor (TNF)-α, contributes to valve disease progression; however, the mechanisms of its actions on cusp retraction and stiffening are unclear. We investigated effects of TNF-α on murine aortic valvular interstitial cells (VICs) within three-dimensional, free-floating, compliant, collagen hydrogels, simulating their natural substrate and biomechanics. TNF-α incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 47 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…Aortic valve leaflets were carefully excised from C57BL/6 mice and cultured via an explant technique, as described previously. 27 Cells were grown in Dulbecco's modified Eagle's medium (DMEM) supplemented with 20% fetal bovine serum (FBS), penicillin, and streptomycin. For osteoblastic differentiation, cells were cultured in alphaminimum essential medium supplemented with 10% FBS (charcoal stripped FBS), 5 mmol/L beta-glycerophosphate and 50 μg/ml of ascorbic acid, and indicated agents.…”
Section: Vic Isolation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic valve leaflets were carefully excised from C57BL/6 mice and cultured via an explant technique, as described previously. 27 Cells were grown in Dulbecco's modified Eagle's medium (DMEM) supplemented with 20% fetal bovine serum (FBS), penicillin, and streptomycin. For osteoblastic differentiation, cells were cultured in alphaminimum essential medium supplemented with 10% FBS (charcoal stripped FBS), 5 mmol/L beta-glycerophosphate and 50 μg/ml of ascorbic acid, and indicated agents.…”
Section: Vic Isolation and Characterizationmentioning
confidence: 99%
“…We next tested the effects on inflammationinduced matrix mineralization of VICs, using the proinflammatory cytokine, TNF-α, which we found to induce matrix mineralization of VIC. 27 VICs were treated with 5-HT and/or TNF-α, and matrix calcification was assessed qualitatively by alizarin red staining and quantitatively by o-cresolphthalein complexone. Results showed that TNF-α-induced matrix mineralization of VIC was augmented by 5-HT ( Figure 2B).…”
Section: Effects Of 5-ht On Tnf-α Induction Of Matrix Mineralizatiomentioning
confidence: 99%
“…Previously considered a degenerative process, cardiovascular calcification is now established as a regulated process ( 1 3 ) in which vascular and valvular mesenchymal cells undergo osteogenic differentiation ( 4 8 ). Clinically, vascular calcification is considered pathognomonic of atherosclerosis.…”
Section: Significance Of Cardiovascular Calcificationmentioning
confidence: 99%
“…39 69 70 Since unopposed positive feedback loops are unstable, some form of negative feedback must also arise, such as the induction of inhibitors like MGP.…”
Section: Positive Feedbackmentioning
confidence: 99%